Ecological Factors Affecting Infection Risk and Population Genetic Diversity of a Novel Potyvirus in Its Native Wild Ecosystem - Rodríguez-Nevado, Cristina; Montes, Nuria; Pagán, Israel (Frontiers in Plant Science, 2017)
Increasing evidence indicates that there is ample diversity of plant virus species in wild ecosystems. The vast majority of this diversity, however, remains uncharacterized. Moreover, in these ecosystems the factors affecting plant virus infection risk and population genetic diversity, two traits intrinsically linked to virus emergence, are largely unknown. Along three years, we have analyzed the prevalence and diversity of plant virus species from the genus Potyvirus in evergreen oak forests of the Iberian Peninsula, the main wild ecosystem in this geographic region and in the entire Mediterranean basin. During this period, we have also measured plant species diversity, host density, plant biomass, temperature, relative humidity and rainfall. Results indicated that potyviruses were always present in evergreen oak forests, with a novel virus species explaining the largest fraction of potyvirus-infected plants. We determined the genomic sequence of this novel virus and we explored its host range in natural and greenhouse conditions. Natural host range was limited to the perennial plant mountain rue (Ruta montana), commonly found in evergreen oak forests of the Iberian Peninsula. In this host, the virus was highly prevalent and was therefore provisionally named mediterranean ruda virus (MeRV). Focusing in this natural host-virus interaction, we analyzed the ecological factors affecting MeRV infection risk and population genetic diversity in its native wild ecosystem. The main predictor of virus infection risk was the host density. MeRV prevalence was the major factor determining genetic diversity and selection pressures in the virus populations. This observation supports theoretical predictions assigning these two traits a key role in parasite epidemiology and evolution. Thus, our analyses contribute both to characterize viral diversity and to understand the ecological determinants of virus population dynamics in wild ecosystems.